Elucidation of Altered Pathways in Tumor-Initiating Cells of Triple-Negative Breast Cancer: A Useful Cell Model System for Drug Screening. (23rd June 2017) - Christensen, Anne G.; Ehmsen, Sidse; Terp, Mikkel G.; Batra, Richa; Alcaraz, Nicolas; Baumbach, Jan; Noer, Julie B.; Moreira, José; Leth-Larsen, Rikke; Larsen, Martin R.; Ditzel, Henrik J.
Abstract : A limited number of cancer cells within a tumor are thought to have self-renewing and tumor-initiating capabilities that produce the remaining cancer cells in a heterogeneous tumor mass. Elucidation of central pathways preferentially used by tumor-initiating cells/cancer stem cells (CSCs) may allow their exploitation as potential cancer therapy targets. We used single cell cloning to isolate and characterize four isogenic cell clones from a triple-negative breast cancer cell line; two exhibited mesenchymal-like and two epithelial-like characteristics. Within these pairs, one, but not the other, resulted in tumors in immunodeficient NOD/Shi-scid/IL-2 Rγ null mice and efficiently formed mammospheres. Quantitative proteomics and phosphoproteomics were used to map signaling pathways associated with the tumor-initiating ability. Signaling associated with apoptosis was suppressed in tumor-initiating versus nontumorigenic counterparts with pro-apoptotic proteins, such as Bcl2-associated agonist of cell death (BAD), FAS-associated death domain protein (FADD), and myeloid differentiation primary response protein (MYD88), downregulated in tumor-initiating epithelial-like cells. Functional studies confirmed significantly lower apoptosis in tumor-initiating versus nontumorigenic cells. Moreover, central pathways, including β-catenin and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB)-related signaling, exhibited increased activation in the tumor-initiating cells. To evaluate the CSC model as a tool for drug screening, we assessed the effect of separately blocking NF-κB and Wnt/β-catenin signaling and found markedly reduced mammosphere formation, particularly for tumor-initiating cells. Similar reduction was also observed using patient-derived primary cancer cells. Furthermore, blocking NF-κB signaling in mice transplanted with tumor-initiating cells significantly reduced tumor outgrowth. Our study demonstrates that suppressed apoptosis, activation of pathways associated with cell viability, and CSCs are the major differences between tumor-initiating and nontumorigenic cells independent of their epithelial-like/mesenchymal-like phenotype. These altered pathways may provide targets for future drug development to eliminate CSCs, and the cell model may be a useful tool in such drug screenings.